Comparative analysis of EGFR mutations in circulating tumor DNA and primary tumor tissues from lung cancer patients using BEAMing PCR - Duhita Mirikar; Nandini Banerjee; Kumar Prabhash; Rajiv Kumar Kaushal; Vanita Naronha; C. S. Pramesh; George Karimundackal; Amit Joshi; Swapnil Rane; Ranjan Basak (Scientific Reports)
Abstract In this study, we measured human epidermal growth factor receptor (EGFR) mutations in both tissue and circulating tumor DNA (ctDNA) by using beads, emulsions, amplifications and magnetic polymerase chain reaction (BEAMing PCR). Noninvasive mutation detection by assessing circulating tumor DNA (ctDNA) offers many advantages over tumor biopsy. One hundred non-small cell lung cancer (NSCLC) patients were enrolled, and both preoperative plasma samples and formalin-fixed and paraffin-embedded (FFPE) samples were collected for the study. The EGFR mutation status was determined by BEAMing PCR in ctDNA. Real-time quantitative PCR (qPCR) data were collected from our hospital database (EMR-qPCR, Electronic Medical Records) for comparative analysis. Additionally, qPCR was also performed on FFPE tissues using a Diatech EGFR qPCR kit. The concordance rates were 98.8%, 98.9% and 95.5% for exons 19, 20 and 21, respectively, when the BEAMing data were compared with the EMR-qPCR data. Additionally, when the BEAMing and Diatech qPCR data were compared, 90%, 100%, 96% and 98% of the genes were obtained for exons 19, 20, 21 (L858R) and 21 (L861Q), respectively. For both comparisons, Cohen’s kappa agreement was significant. The advantage of BEAMing is its ability to identify mutated DNA sequences in cancer cells in the background of normal cell DNA contamination. This could be useful for disease monitoring and progression.